1999
DOI: 10.3109/15419069909034395
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Integrin and Receptor Tyrosine Kinase Genes During Autograft Fusion in the SpongeGeodia cydonium

Abstract: Recently cDNAs coding for cell surface molecules have been isolated from sponges. The molecules for a-integrin, galectin, and receptor tyrosine kinase (RTK), obtained from the marine sponge, Geodia c-vdonium, have been described earlier. In the present study also the cDNA for one putative P-integrin has been identified from G. cydonium. The deduced aa sequence comprises the characteristic signatures, found in other metazoan /3-integrin molecules; the estimated size is 95,215 Da. To obtain first insights into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 58 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…The sources of chemicals and enzymes used have been given previously Wimmer et al, 1999a;Krasko et al, 2000). The 'Cell Death Detection ELISA plus' kit and the PCR-DIG-Probe were from Roche (Mannheim, Germany), and all-trans retinoic acid and poly-L-lysine (Mr 30·000-70·000) from Sigma (Deisenhofen, Germany).…”
Section: Chemicals and Enzymesmentioning
confidence: 99%
“…The sources of chemicals and enzymes used have been given previously Wimmer et al, 1999a;Krasko et al, 2000). The 'Cell Death Detection ELISA plus' kit and the PCR-DIG-Probe were from Roche (Mannheim, Germany), and all-trans retinoic acid and poly-L-lysine (Mr 30·000-70·000) from Sigma (Deisenhofen, Germany).…”
Section: Chemicals and Enzymesmentioning
confidence: 99%
“…71 Polyclonal antibodies against rBHP2GC were raised in rabbits as described. 72 Purified rBHP2GC (3610 mg of protein) was injected; after 15-weeks serum was collected and the antibodies were prepared; 73 they are termed PoAb-BHP2GC. In control experiments 100 ml of the PoAb-BHP2GC were adsorbed to 50 mg of rBHP2GC (30 min; 48C) prior to its use.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…In parabiotic grafting experiments it has been shown that the intraspecific variability of AFs rivals that of the vertebrate MHC; any two individuals rejecting each other have different genomic sequences for AF proteins as indicated by restriction fragment length polymorphism analysis (19,22). Other molecules involved in cell-ECM interactions such as ␣ and ␤ integrins and the hyaluronan receptor CD44 have been found to be differentially expressed in sponge isografts and allografts (7,23). Elevated integrin expression in the absence of appropriate ligands can promote apoptosis under otherwise permissive growth conditions (24).…”
mentioning
confidence: 99%